Review of the collection of underwings Catocala Schrank, 1802 (Lepidoptera: Erebidae: Erebinae: Catocalini) of the Museum of Nature of the V. N. Karazin Kharkiv National University - Guglya, Yu. O.; Geryak, Yu. M. (The Kharkiv Entomological Society Gazette, 2022)
A complete annotated list of the underwings Catocala Schrank, 1802 (Lepidoptera: Erebidae: Erebinae: Catocalini) of the lepidopterological collection of the Museum of Nature of V. N. Karazin Kharkiv National University is provided. In general, the Museum’s collection of underwings consists of 603 specimens of 48 species collected over the past 140 years in Ukraine and several other countries, mainly in the territory of the former USSR. Among them, Catocala lesbia Christoph, 1887 recorded for the first time in Armenia, C. afghana Swinhoe, 1885 — in Uzbekistan, and C. conversa (Esper, 1783) — in Kharkiv Region of Ukraine. At the same time, several species presented in the collection are generally little-known, locally distributed and rare. 16 figs, 6 refs.
Keywords: Catocala; Erebidae; Lepidoptera; annotated list; catalog; collection